The Economic Impact of Land Acquisition for Industrial Projects - N Subbukrishna Sastry; Manjula Mallya M (International Journal of Land, 2025)
Land acquisition for industrial projects plays a crucial role in promoting economic development, yet it often leads to significant socio-economic challenges. In India, land acquisition is regulated under the Right to Fair Compensation and Transparency in Land Acquisition, Rehabilitation and Resettlement Act, 2013. While this legislation aims to ensure fair compensation, transparency, and proper rehabilitation for affected individuals, its implementation often faces significant hurdles. Prolonged administrative delays, ongoing legal battles, and socio-economic challenges frequently complicate the acquisition process, affecting both development projects and the communities involved. In contrast, foreign countries employ diverse approaches—ranging from streamlined eminent domain procedures in the United States to participatory planning and technological integration in the European Union, Australia, and Canada—resulting in faster project implementation, predictable costs, and better community integration. This study critically examines the economic impact of land acquisition for industrial purposes in India, comparing it with international practices to identify gaps, challenges, and potential policy improvements. The aim of researchers in their research to provide actionable insights for policymakers, industrial planners, and researchers, emphasizing strategies that minimize socio-economic displacement while facilitating sustainable industrial growth. Moreover, the Act’s requirement for detailed social impact assessments, consent from affected landowners, and multiple approval stages often makes the acquisition process time-consuming. While these measures aim to protect communities, they can also complicate project timelines, especially for infrastructure and industrial development
Keywords: India; Land acquisition; comparative analysis; economic impact; industrial projects; policy intervention; socio-economic effects